SEM analysis of Mtwo instruments after instrumentation of root canals with different curvatures - Jovanović-Medojević Milica (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction Deformations and fractures of Ni-Ti instruments during chemomechanical instrumentation of root canals occur due to the action of cyclic and torsional forces. The aim of this research was to analyze the surfaces of the working parts of Mtwo instruments after preparation of root canals with different curvatures using SEM and determine possible changes and deformations after instrumentation. Materials and methods The study included 3 sets of Mtwo (VDW, Munich, Germany) instruments. Each set was used to instrument 10 canals in three experimental groups (straight, slightly curved, and highly curved canals). Instrumentation was carried out using crown-down technique with the following irrigation solutions, 2% NaOCl (CHLORAXID 2%, Cerkamed, Polska) and Distilled water (Iva, Serbia) in the amount of 5 cm³. The apical and middle third of the instruments were scanned in two directions using SEM at different magnifications (150-2000X). The SEM images were analyzed using qualitative analysis for the presence of different irregularities according to Eggert et al. Statistical analysis of obtained data was performed using Fisher test at a confidence level of 5% ( a = 0.05). Results Most defects (37.3%) were observed in instruments used in highly curved canals, followed by the instruments of the second group (35.6%), and the least defects were (27.1%) observed in the group with straight canals. Higher prevalence of defects was observed in the apical thirds of instruments (54.2%), especially in the experimental group of curved canals where the highest presence was observed (20.3%). The presence of production grooves was observed in all instruments, and the most common types of defects after instrumentation were the appearance of corrosion and changes in the cutting edges. In the group with extremely curved canals fractures were observed in two instruments (10/0.04 and 15/0.05). Conclusion Root canal curvature significantly affects the occurrence of deformations and fractures of Ni-Ti rotating instruments. The most common types of defects were grooves, corrosion and changes in the blade edges. Mtwo instruments showed deformations in terms of thread changes, microfractures and two complete fractures.